Analysis method of matrix and second phase particles in Zircaloy-2 by atom probe tomography. (July 2015) - Sawabe, T.; Sonoda, T.; Kitajima, S.
Abstract: Properties of second-phase particles (SPPs) influence the corrosion resistance and the anti-hydrogen pickup in Zircaloy-2 claddings. The chemical compositions of Zr(Fe, Cr)2 and Zr2 (Fe, Ni) SPPs were investigated by means of pulsed laser atom probe tomography. In order to identify the atomic concentration with accuracy, two approaches were applied to the Zr-matrix and the SPPs: the first by using all the visible peaks of the mass spectrum and the second using the representative peaks with the natural abundance of the corresponding isotopes. It was found that the background and tail effects are minimized by the first approach in case of estimating a single phase. The change in the concentration between the Zr-matrix and the SPPs can be estimated more accurately by the second approach, although Sn concentration in the Zr2 (Fe, Ni) SPPs is slightly overestimated. Highlights: Matrix and second phase particles (SPPs) were analyzed by atom probe tomography. Two approaches were applied for estimation of the chemical compositions. Using all visible peaks in the mass spectrum decreased the background and peak tail effects. Using the representative peaks and the natural abundance could estimate two phases in the same time.